Endurance training induced cellular electrophysiological remodeling in a small and a large animal athlete's heart model. (19th May 2022) - Topal, T; Polyak, A; Toth, N; Zombori-Toth, N; Deri, SZ; Virag, L; Jost, N; Farkas, A; Baczko, I; Farkas, AS; Varro, A
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Funding: It was supported by NKFIH grants (K-19992, K- 135464, GINOP-2.3.2-15-2016-00047). Background: The positive impact of regular exercise on a healthy and fulfilling lifestyle. Therefore, active athletes are considered the healthiest members of our society. However, there is an increasing amount of evidence that long-term high-intensity sporting activity could also have adverse effects on the heart, such as impaired electrophysiological properties. Heavy long-term training can lead to structural and functional remodelling of the heart, which in turn, can evoke malignant cardiac arrhythmias. Purpose: To develop animal models with a significant translational value of the human athlete's heart and to investigate underlying malignant drivers of cardiac arrhythmias due to the long-term endurance training in in vitro studies. Methods: 24 dogs from both sexes and 26 male guinea pigs were randomly assigned to sedentary ('Sed') and trained ('Tr') groups (n = 12-12; n=13-13). The latter group underwent a long-term endurance interval-training program on the treadmill 5 days a week for 4 months. ECG recordings and echocardiography validated the characteristic of athlete's heart. After heart removal, the degree of interstitial fibrosis was quantified and ventricular myocytes were enzymatically dissociated via retrograde perfusion. The transmembrane ionic currents were recorded using the whole-cell configuration of the patch-clamp technique. The action potentials were measured by the perforated patch-clamp technique. Immunocytochemistry measurements were performed to determine the density of transmembrane ion channels. Results: Based on the ECG and ECHO results, the vigorous training program resulted in significant cardiac adaptation in both species. In addition, it caused mild ventricular fibrosis. The repolarization is reflected as the 90 percent of action potential duration (APD90). It was significantly lengthened in the left ventricular myocytes of 'Tr' dogs. ('Tr' vs. 'Sed' 472.8±29.6 ms; =29 vs. 369.3±31.4 ms; n=24, p=0.023) and there was no difference in the case of guinea pigs. The amplitude of the transient outward current (Ito), which is not expressed in the guinea pig heart, was significantly smaller in the 'Tr' dogs ('Tr' vs. 'Sed' 7.6±0.6 pA/pF, n=54 vs. 10.2±1.0 pA/pF, n=42, p<0.05). Under the currently used protocols, no differences were detected in the magnitude of other ionic currents. The HCN4 gene expression was significantly higher in isolated myocytes in 'Tr' dogs. Conclusion: Increased ectopic activity is not rare among top athletes. Our results suggest an association between increased arrhythmia susceptibility and impaired repolarisation reserve related to down-regulation of Ito and prolonged APD90 and enhanced fibrotic changes. The overexpression of HCN4 gene in hypertrophic hearts, similar to heart failure, may evoke malignant ventricular arrhythmias. Further studies are warranted to clarify this hypothesis in more detail.